2022
DOI: 10.3390/v14050848
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Skin- and Neuro-Attenuated Live Varicella Vaccine: A Review and Future Perspectives

Abstract: Primary varicella-zoster virus (VZV) infection causes varicella, which remains a prominent public health concern in children. Current varicella vaccines adopt the live-attenuated Oka strain, vOka, which retains the ability to infect neurons, establish latency and reactivate, leading to vaccine-associated zoster in some vaccinees. Therefore, it is necessary to develop a safer next-generation varicella vaccine to help reduce vaccine hesitancy. This paper reviews the discovery and identification of the skin- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In the preclinical immunogenicity evaluations, the same doses of v7D and vOka induce similar VZV-specific antibody and T-cell responses in mice, rats, guinea pigs and rabbits, suggesting that the immunogenicity of v7D vaccine is comparable to that of vOka in these small animal models. 20 In addition, v7D is well-tolerated and immunogenic in non-human primates. 19 , 20 The present study is a randomized, double-blind, controlled, dose-escalation and age de-escalation phase 1 trial in China (ChiCTR1900022284) designed to assess the safety and immunogenicity of the freeze-dried v7D candidate varicella vaccine in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the preclinical immunogenicity evaluations, the same doses of v7D and vOka induce similar VZV-specific antibody and T-cell responses in mice, rats, guinea pigs and rabbits, suggesting that the immunogenicity of v7D vaccine is comparable to that of vOka in these small animal models. 20 In addition, v7D is well-tolerated and immunogenic in non-human primates. 19 , 20 The present study is a randomized, double-blind, controlled, dose-escalation and age de-escalation phase 1 trial in China (ChiCTR1900022284) designed to assess the safety and immunogenicity of the freeze-dried v7D candidate varicella vaccine in humans.…”
Section: Introductionmentioning
confidence: 99%
“… 20 In addition, v7D is well-tolerated and immunogenic in non-human primates. 19 , 20 The present study is a randomized, double-blind, controlled, dose-escalation and age de-escalation phase 1 trial in China (ChiCTR1900022284) designed to assess the safety and immunogenicity of the freeze-dried v7D candidate varicella vaccine in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, the VZV vaccine still has some drawbacks. Most of the current varicella vaccines use the vaccine Oka, which still has the ability to infect neurons and reactivate, resulting in vaccine-induced VZV in some vaccinators [ 11 ]. In addition, some evidences have suggested that the immune response obtained from the vaccine diminishes over time [ 12 ].…”
Section: Introductionmentioning
confidence: 99%